Non-stress test, amniotic fluid index and color of liquor in term pregnancies in active labour and their association with labour and perinatal outcome - George, Divya; Daniel, Shiny; Krishnan, Anoop (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The features of amniotic fluid, such as volume and color, are essential for evaluating fetal health and forecasting postnatal outcomes. Oligohydramnios and meconium-stained amniotic fluid correlate with a heightened risk of unfavorable newborn outcomes, such as diminished APGAR scores, increased NICU hospitalizations and cesarean sections. The non-stress test (NST) is an essential instrument for assessing fetal discomfort during childbirth. This research sought to evaluate the predictive significance of the amniotic fluid index (AFI), wine color and non-stress test (NST) in forecasting newborn outcomes in term pregnancies. Methods: This comparative prospective cross-sectional research was performed at the Obstetrics and Gynaecology Department of teaching hospitals associated with J.J.M. Medical College, Davangere, from March 2021 to August 2022. A total of 100 term pregnant women in active labor were enrolled. Clinical and ultrasonographic evaluations were conducted to examine Amniotic Fluid Index (AFI), non-stress test (NST) reactivity and liquor properties. Neonatal outcomes, including APGAR scores, birth weight, NICU hospitalizations and delivery method, were documented. Data were evaluated using SPSS v22.0, with statistical significance established at p<0.05. Results: Maternal age had a significant correlation with meconium-stained liquid (p=0.026), although other maternal factors, including parity, gestational age and BMI, shown no significant variations. The non-reactivity of NST was markedly elevated in the meconium-stained liquor groups (thin: 50%, thick: 33.33%) in contrast to the clear liquor group (16%) (p=0.011). A low amniotic fluid index (AFI) (<8 cm) was more common in the thin meconium-stained liquid group (75%) compared to the clear (54.67%) and thick meconium-stained groups (22.2%). The group with thick meconium staining had markedly lower mean APGAR scores at 1 minute (5.89±0.98) in comparison to the thin (6.47±2.05) and clear liquor groups (6.87±1.21) (p=0.007). NST, AFI and liquor color exhibited significant correlations with cesarean delivery, NICU hospitalization and infant morbidity. The predictive sensitivity of liquor volume, liquor hue and NST for neonatal problems was 77.78%, 80% and 81.82%, respectively. Conclusions: NST, AFI and amniotic fluid color are significant indicators of fetal well-being in term pregnancies. The occurrence of oligohydramnios, abnormal NST and meconium-stained amniotic fluid markedly elevates the probability of negative outcomes, including as surgical delivery and diminished APGAR scores. These results highlight the need of ongoing intrapartum fetal surveillance and prompt management in high-risk pregnancies.